STRATEGY OF DAKWAH KIAI ANWAR IN MULTICULTURAL SOCIETY IN BADUNG, BALI - IDA SELVIANA MASRUROH (Indonesian Journal of Islamic Communication, 2022)
Da'wah is the process of encouraging humans to do good and forbid from munkar deeds with the aim of getting the happiness of the world and the afterlife. This research focused on Kiyai Anwar Hamid's da'wah strategy on hindu and Muslim communities in Bali to maintain harmony between religious people, especially in the Kuta Badung area. This study focused on the formulation of other problems: How is kiyai Anwar Hamid's Da'wah Method in maintaining harmony between people in hindu and Muslim communities in Kuta Bali? In identifying this problem, researchers use a Descriptive Qualitative approach with data collection techniques using observation then Interviews and documentation. So in this study produced a conclusion: Kiyai Anwar Hamid's da'wah strategy uses Da'wah Bil Hal, Bil Lisan and not in a harsh way in conveying kindness.